Pelatihan Transformasi Digital dalam Pengelolaan SDM bagi UMKM Koperasi Merah Putih Di Kecamatan Gunungsari Kabupaten Lombok Barat - Dhiyas Ainun Safitri; Firman Suratulloh; Anugrah Rizki Seno Aji (Journal of Community Action, 2025)
Digital transformation training in Human Resources (HR) management for the Red and White Cooperative MSMEs in Gunungsari District aims to increase the efficiency of HR management through the use of digital technology. Most cooperative members have not adopted digital technology in managing human resources, which results in administrative processes and decision making that are slow and prone to errors. For this reason, this training focuses on understanding and skills in using digital-based HR management applications, which include recording attendance, managing salaries, and preparing financial reports. The training method used is a workshop approach and direct training with theory and practical sessions. Participants are taught how to operate HR management applications, and are given case studies to practice applying technology in everyday contexts. The results of the training showed a significant increase in participants' understanding and skills regarding digital technology in HR management. Although there are challenges in full implementation in the field, it is hoped that this training can accelerate digital transformation in MSMEs and cooperatives, as well as increase sustainable operational efficiency. This training program also has the potential to become a model for the development of other MSMEs in the region.